Palynology of the Jagüel Formation (Maastrichtian–Danian) in northwestern Río Negro, Neuquén Basin, Argentina: paleobiogeographic inferences - Perez Pincheira, Egly Veronica; Di Pasquo Lartigue, Maria (Cretaceous Research)
The palynology of the Jagüel Formation at Cerro Azul locality Río Negro province; in the Neuquén Basin, was studied. The distribution of palynomorphs (spores, pollen grains, chlorophytes, and miscellaneous forms) across the outcrops allowed the definition of three palynological associations: A1 (upper Maastrichtian), A2 and A3 (Danian). The palynological results, together with micro- and invertebrate fossils found in this locality contributed to the paleoenvironmental reconstruction of this unit. A1 is deposited in mixed (coastal) to shallow marine environments with low energy associated to freshwater bodies. Whereas it is interpreted that A2 and A3 are deposited in coastal lagoons near shallow and internal platform marine environments. The largest number of palm pollen grains of Proxapertites and other angiosperms Retitrescolpites baculatus and Striatopollis for the Danian of Argentina has been registered here. These associations shared species with Maastrichtian and Danian palynofloras of the Colorado and western Neuquén basins. Species with affinities from northern latitudes of South America and Africa, and a few other species distributed more widely (cosmopolitan) and from southern regions (Argentina, Chile, Antarctica, New Zealand) predominate in the Danian. Therefore, we can confirm that the palynofloras of the Jagüel Formation are part of the Mixed Floristic Realm. Fil: Perez Pincheira, Egly Veronica. Provincia de Entre Ríos. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción. Universidad Autónoma de Entre Ríos. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Santa Fe. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción; Argentina Fil: Di Pasquo Lartigue, Maria. Provincia de Entre Ríos. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción. Universidad Autónoma de Entre ...